Nanoparticle technology in Aqueous Carbon Dioxide (CO2) foam for Enhanced Oil Recovery (EOR) / Azwan Harun … [et al.] - Harun, Azwan; Tengku Mohd, Tengku Amran; Alias, Nur Hashimah; Ghazali, Nurul Aimi; Azizi, Azlinda (Research Innovation Business Unit, 2014)
Foam Flooding is an established Enhanced Oil Recovery (EOR) approach to recover the remaining oil in the reservoir, which is implemented after primary and secondary recovery. However, foam flooding faces various problems due to low viscosity effect, which reduces its efficiency in recovering oil. The biggest challenge is to produce longer lasting foam while injecting to the reservoir for oil displacement. Foam stability can be uttered in foamability measurement and bubble size dispersal. The higher the foamability, the more stable it is. Using surfactant to stabilize CO2 foam may reduce mobility and improve areal and vertical sweep efficiency, but the potential weaknesses are such that high surfactant retention in porous media and unstable foam properties under high temperature reservoir conditions. Thus, this research aimed to investigate the stability and foamability of CO2 foam with addition of nanoparticle, the optimum surfactant and nanoparticle concentration with highest foam stability and determine the relationship between the foamability and the nanoparticle concentration within the carbon dioxide foam system. Foam generator has been used to generate CO2 foam and analyse its stability and foamability under varying parameters. Surfactant solutions were prepared within 500 ppm to 5000 ppm, which was investigated at different nanoparticle concentrations from 1000 ppm to 5000 ppm. Foam stability and foamability were investigated through observation of the foam bubble size and the reduction of foam height inside the observation tube. It was found that increases of surfactant and nanoparticle concentration have boosted up the stability of the foam produced from 92% to 100% foamability and foam durability was extended up to 5 hours. The optimum concentration of both surfactant and nanoparticle was found at 5000 ppm. Liquid with the presence of both silica nanoparticle and surfactant generated more stable foam with lower mobility as the mixture reduced interfacial tension (IFT) between CO2 and water; also strengthen the adhesive and cohesive force inside the lamella of the foam. Addition of Nano silica particle to the foam system has improved the rigidity of the lamellae interface and prevents it from rupture. Relationship between foamability and nanoparticle concentration has been determined in forecasting the foam stability, mobility and morphology with the newly breakthrough nanoparticle technology. In conclusion, novel stabilized aqueous CO2 foam with addition of nanoparticle can be potential candidate for foam flooding application and commercialization. The relationship could provide a cost-effective planning for foam flooding with addition of nanoparticle in combination of surfactant. This potential EOR research is closely related to one of the National Key Economic Areas (NKEAs), Oil, Gas and Energy, which has been attractive business contributing to socio-economy to the country such as reducing dependence on foreign oil, supporting job creation, increasing tax revenue and economic growth. Moreover, the recent 30-year deal between Petronas and Shell Malaysia for the implementation of the world’s largest EOR projects in Malaysia proved that Malaysia is getting towards commercializing EOR projects. Thus, the application of nanoparticle technology in foam flooding to produce longer lasting foam with high stability and foamability is believed to offer good future in EOR projects aligned with the industrial technology development to be commercialized.